Excretory/secretory proteins inhibit host immune responses by downregulating the TLR4/NF-κB/MAPKs signaling pathway: A possible mechanism of immune evasion in parasitic nematode Haemonchus contortus - Wen, Zhaohai; Zhang, Yue; Feng, Jiajun; Aimulajiang, Kalibixiati; Aleem, Muhammad Tahir; Lu, Mingmin; Xu, Lixin; Song, Xiaokai; Li, Xiangrui; Yan, Ruofeng (Frontiers in Immunology, 2022)
Haemonchus contortus is an important parasitic nematode of ruminants and used as a model for animal parasite research. Previous study showed that H. contortus escape the immunity through complex mechanisms, including releasing excretory and secretory proteins (ESPs) to modulate the host immune response. However, the detailed mechanism for H. contortus excretory and secretory proteins (HcESPs) promote immune evasion in H. contortus remains unknown. In the present study, we demonstrated that HcESPs inhibit the adaptive immune response of goat include downregulation of immune cell antigen presentation, upregulation of immune checkpoint molecules, activation of the STAT3/PD-L1 pathway, and activation of immunosuppressive regulatory T (Treg) cells. Furthermore, HcESPs reversed the LSP-induced upregulation of pro-inflammatory mediators in PBMCs by inhibition of the TLR4/NF-κB/MAPKs/NLRP3 signaling pathway. Our study provides a better understanding of the evasion mechanisms for H. contortus，the finding could be helpful in providing alternative way to prevent the infection of this parasite. Keywords: Haemonchus contortus; HcESPs; PBMCs; TLR4/NF-κB/MAPKs signaling pathway; immune evasion; pattern recognition receptor.